2021
DOI: 10.1371/journal.pone.0249736
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of hemorrhoids among adult patients visiting the surgical outpatient department in the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia

Abstract: Introduction Hemorrhoidal disease is a very common benign anorectal disease. It affects millions of people around the world, and represent a major medical and socioeconomic problem. However, studies that determine the magnitude and risk factors are limited. Therefore, the aim this study is to assess the prevalence and associated factors of hemorrhoid among adult patients visiting the surgical outpatient department at the University of Gondar Comprehensive Specialized Hospital (UoGCSH) Northwest Ethiopia. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
0
6

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 23 publications
8
37
0
6
Order By: Relevance
“…The most common perianal condition in this study was fistula in ano unlike studies from Nepal, India, Romania and Iran in which haemorrhoids was the leading pathology ( 15 – 18 ). The male predominance that was seen in our study in patients with fistula in ano as well as haemorrhoids was in line with studies from India, Egypt, Turkey, United Kingdom and Gonder ( 16 , 19 – 22 ).…”
Section: Discussionsupporting
confidence: 92%
“…The most common perianal condition in this study was fistula in ano unlike studies from Nepal, India, Romania and Iran in which haemorrhoids was the leading pathology ( 15 – 18 ). The male predominance that was seen in our study in patients with fistula in ano as well as haemorrhoids was in line with studies from India, Egypt, Turkey, United Kingdom and Gonder ( 16 , 19 – 22 ).…”
Section: Discussionsupporting
confidence: 92%
“…Sebuah penelitian epidemiologi oleh Johanson et al pada tahun 1990 silam memperlihatkan persentase prevalensi sebesar 4,4% di Amerika Serikat dengan angka yang mencapai 10 juta keluhan. 5,10 Sementara itu, beberapa laporan penelitian pada abad ke-21 menunjukkan persentase prevalensi sebesar 14,4% dan 38,9% dari Korea Selatan dan Austria. 10 Terlepas dari minimnya efek samping dan alamiahnya bahan yang digunakan dalam obatobat tradisional, hemoroid masih merajalela di negara-negara bagian Asia Timur yang kerap mempraktikkan pengobatan tradisional.…”
Section: Epidemiologi Hemoroidunclassified
“…According to a study done at Ayder Referral Hospital, internal hemorrhoids was the third most common (7.5%) colonoscopic finding [ 3 ]. Another study conducted at University of Gondar comprehensive specialized hospital showed that 13.1% of adult patients who visited the surgical outpatient department had hemorrhoids [ 4 ]. Abdissa et al.…”
Section: Introductionmentioning
confidence: 99%
“…According to a study done at Ayder Referral Hospital, internal hemorrhoids was the third most common (7.5%) colonoscopic finding [3]. Another study conducted at University of Gondar comprehensive specialized hospital showed that 13.1% of adult patients who visited the surgical outpatient department had hemorrhoids [4]. Abdissa et al [5] also showed that constipation due to hemorrhoids was responsible for one-fourth (24.4%) of the patients in the obstetric ward of Jimma University medical center to seek nursing cares.…”
Section: Introductionmentioning
confidence: 99%